Antibacterial packaging material and preparation method thereof

By mixing functional Ellow nano tubes with modified polyethylene, heating membranes, and producing antibacterial packaging materials, the problems of insufficient anticoor static, antibacterial and degradable performance in existing technologies have achieved efficient static elimination , Antibacterial effect and degradability.

CN119371752AInactive Publication Date: 2025-01-28SHENZHEN GUOSHENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411719047.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve antistatic, antibacterial and degradable packaging material properties simultaneously, especially in the absence of electrostatic and microbial contamination.

Method used

By mixing the functional Ellow nano tube with the modified polyethylene, heating the membrane, which is made of antibacterial packaging materials. Functional Ellow nano -pipes form a MOF structure through tea polyphenol load and surface reaction to enhance antioxidant and flame retardant performance. Modified polyethylene is formed through phosphorus branches and ductinium salts to improve antibacterial and flame retardant performance.

Benefits of technology

Anti -static, antibacterial, and degradable packaging materials are realized, the flame retardant capacity and long -acting antioxidant performance of the material are enhanced, and the degradability of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157570780000121
    Figure BDA0005157570780000121
Patent Text Reader

Abstract

The invention discloses an antibacterial packaging material and a preparation method thereof, and relates to the field of high polymer materials. When the antibacterial packaging material is prepared, polyethylene sequentially reacts with 3-bromo-1-propylene and amino trimethylene phosphonic acid, and modified polyethylene is prepared; the preparation method comprises the following steps: etching a halloysite nanotube with a hydrochloric acid solution, loading tea polyphenol into the halloysite nanotube, reacting 4-(3-thienyl) benzaldehyde and pyrrole on the surface of the halloysite nanotube, and finally polymerizing with 3-aminothiophene and thiophene to prepare the functionalized halloysite nanotube. And mixing the functionalized halloysite nanotube and the modified polyethylene, heating, and preparing a film, thereby obtaining the antibacterial packaging material. The antibacterial packaging material prepared by the invention has the capabilities of flame retardance, static electricity resistance, degradability and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to an antibacterial packaging material and a preparation method thereof. Background Art

[0002] Among the many materials that support the development of our society, carbon-based materials play a vital role. Since thermoplastic polymers are low-cost, easy to shape and can be reused, they are widely used in various aspects of production and life such as food packaging and pipeline transportation. Among them, polyethylene is one of the most widely used carbon-based materials. Polyethylene is a thermoplastic resin made by polymerization of ethylene monomer. In industry, it also includes copolymers of ethylene and a small amount of a-olefins. Polyethylene is odorless, non-toxic, feels like wax, has excellent low-temperature resistance, and has good chemical stability. Because the polymer molecules are connected by carbon-carbon single bonds, they can withstand most acid and alkali corrosion, are insoluble in general solvents at room temperature, and have low water absorption. Polyethylene has a wide range of uses, mainly used to make films, packaging materials, containers, pipes, monofilaments, wires and cables, daily necessities, etc. With the development of petrochemicals, polyethylene production has developed rapidly.

[0003] With the continuous development of polymer composite technology and the popularization of environmental protection concepts, people have continuously put forward higher requirements for the performance of materials, and the application of packaging materials with excellent comprehensive performance has also been expanding. In order to adapt to market demand, the development and application of green functional packaging materials has become the main direction of the modern packaging industry. Static electricity, as a near-field natural hazard, has been prevalent in many industries, such as aerospace, national defense, petrochemical and other industries. In many industries, if some sensitive instruments are used, static spark discharge will occur when the accumulated static charge reaches a certain level. This discharge is a random process of instantaneous energy release. The electromagnetic pulses and discharge currents generated will cause great harm to electronic devices. If this phenomenon is not taken seriously, the losses to mankind will be huge. In addition, electronic components, semiconductor materials and other materials may be contaminated by microorganisms during transportation. Therefore, this article introduces a green, degradable and antibacterial packaging material with antistatic ability. Summary of the invention

[0004] The object of the present invention is to provide an antibacterial packaging material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] An antibacterial packaging material is prepared by mixing functionalized halloysite nanotubes and modified polyethylene, heating, and forming a film;

[0006] The modified polyethylene is prepared by reacting polyethylene with 3-bromo-1-propylene and aminotri(methylenephosphonic acid) in sequence;

[0007] The functionalized halloysite nanotubes are prepared by etching the halloysite nanotubes with hydrochloric acid solution, loading tea polyphenols inside the halloysite nanotubes, reacting 4-(3-thienyl)benzaldehyde and pyrrole on the surface of the nanotubes, and finally polymerizing with 3-aminothiophene and thiophene.

[0008] A method for preparing an antibacterial packaging material, the method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0009] (1) Take 40-60 parts of polyethylene, 90-110 parts of xylene, 3-4 parts of diisopropylbenzene peroxide, and 8-10 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 70-80°C and 200-300 r / min for 10-20 min, raise the temperature to 120-140°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 10-30 min, stir at 250-350 r / min for 30 min. ~4h, cooled to room temperature, filtered, washed with acetone 3~5 times, vacuum dried at -10~0℃ for 22~26h, crushed to 30~50 mesh, and obtained pre-modified polyethylene; pre-modified polyethylene, aminotri(methylenephosphonic acid) and N-methylpyrrolidone were mixed in a mass ratio of 4~6:1:10~20, stirred at 200~300r / min, 70~90℃ for 10~14h, filtered, washed with methanol 3~5 times, vacuum dried at -10~0℃ for 22~24h, and obtained modified polyethylene;

[0010] (2) mixing halloysite nanotubes with hydrochloric acid solution in a mass ratio of 1:15-17, stirring at 70-90°C and 200-300 r / min for 7-9 hours, filtering, washing with deionized water for 3-5 times, vacuum drying at -10-0°C for 22-26 hours, grinding to 80-120 meshes, and obtaining halloysite nanotube powder; mixing halloysite nanotube powder, deionized water and tea polyphenols in a mass ratio of 1:8-12:2-3, and evaporating at 0-4°C. The method comprises the following steps: ultrasonicating for 25 to 35 minutes, standing under vacuum for 25 to 30 minutes, returning to normal pressure, repeating the operation 2 to 4 times, centrifuging at 5000 r / min for 4 to 6 minutes, washing with ethanol for 3 to 5 times, vacuum drying at -10 to 0°C for 11 to 13 hours, grinding to 30 to 50 meshes, and preparing pre-modified halloysite nanotubes; mixing the pre-modified halloysite nanotubes, 4-(3-thienyl)benzaldehyde and propionic acid in a mass ratio of 30 to 40:16 to 20 : 200-210, stir at 138-142°C, 200-300r / min for 3-5min, add 0.11-0.12 times the volume of propionic acid in pyrrole mixture at a uniform rate within 25-35min, continue stirring for 100-140min, cool to room temperature, add 1.13-1.15 times the volume of propionic acid in ethanol, let stand at 0-4°C for 22-26h, filter, wash with ethanol 3-5 times, and freeze at -10-0°C The modified halloysite nanotubes were prepared by vacuum drying for 22 to 24 hours; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 1:3 to 5:2 to 3:1 to 9 to 11, stirred for 8 to 10 minutes at 30 to 40°C, 200 to 300 r / min, and nitrogen protection, filtered, allowed to stand at 50 to 60°C for 10 to 14 hours, and washed with deionized water for 3 to 5 times to obtain functionalized halloysite nanotubes;

[0011] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water are mixed in a mass ratio of 1:5-7:60-65:2.5-3.5, stirred at 200-300 r / min and 85-95° C. for 3.5-4.5 h, filtered, washed with ethanol 3-5 times, dried, heated to 120-140° C., ultrasonicated for 8-10 min, and film-formed to obtain an antibacterial packaging material.

[0012] As an optimization, the concentration of the hydrochloric acid solution in step (2) is 4M.

[0013] As an optimization, the tea polyphenols in step (2) are 98% water-soluble tea polyphenols, and the manufacturer is Gansu Yishengxiang Biotechnology Co., Ltd.

[0014] As an optimization, the pyrrole mixed solution in step (2) is prepared by uniformly mixing pyrrole and propionic acid in a volume ratio of 6-8:9-11.

[0015] As an optimization, the repeated operation in step (2) refers to repeatedly standing under vacuum conditions for 25 to 30 minutes and restoring to normal pressure.

[0016] As an optimization, the specific operation of the film-making in step (3) is to evenly coat the film on the surface of a clean glass sheet with a thickness of 0.03 to 0.05 mm, let it stand for 22 to 26 hours, and then scrape it off.

[0017] As an optimization, the specific operation of the drying in step (3) is drying at 85-95° C. for 22-26 hours.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] When preparing the antibacterial packaging material, the present invention comprises the following steps: after the halloysite nanotube is etched with a hydrochloric acid solution, tea polyphenol is loaded into the interior of the halloysite nanotube; 4-(3-thienyl)benzaldehyde and pyrrole are reacted on the surface of the halloysite nanotube; finally, the nanotube is polymerized with thiophene to obtain the functionalized halloysite nanotube; polyethylene is reacted with 3-bromo-1-propylene and aminotri(methylenephosphonic acid) acid in sequence to obtain the modified polyethylene; the functionalized halloysite nanotube and the modified polyethylene are mixed, heated, and film-formed to obtain the antibacterial packaging material.

[0020] After the halloysite nanotubes are etched with a hydrochloric acid solution, tea polyphenols are loaded into the interior of the halloysite nanotubes, and then 4-(3-thienyl)benzaldehyde and pyrrole are reacted on the surface, and finally polymerized with thiophene to obtain functionalized halloysite nanotubes; tea polyphenols have a good antioxidant effect, and the specific surface area of ​​the halloysite nanotubes after acid etching is increased, so that more phenolic substances in tea polyphenols can be loaded inside them, achieving the effect of long-term slow release of antioxidants; the halloysite nanotubes absorb a large amount of heat through endothermic decomposition during the combustion process, thereby reducing the surface temperature of the material and slowing down thermal cracking The reaction speed is increased, the generation of flammable gases is suppressed, and the flame retardancy of the material is enhanced; 4-(3-thienyl)benzaldehyde and pyrrole are then reacted on its surface to form a MOF deconstruction, and finally polymerized with 3-aminothiophene and thiophene to form a polythiophene polymer on the surface of the halloysite nanotubes. As a conductive polymer, polythiophene can absorb and transfer charges through its electrical conductivity and high conductivity, reduce the cumulative effect of static electricity, and thus achieve an antistatic effect; and the iron ions in the ferric chloride catalyst used for polythiophene polymerization can combine with the MOF structure and degrade the polymer under photocatalysis.

[0021] Polyethylene is reacted with 3-bromo-1-propylene and aminotri(methylene)phosphonic acid in sequence to obtain modified polyethylene; functionalized halloysite nanotubes and modified polyethylene are mixed, heated, and film-formed to obtain antibacterial packaging materials; polyethylene is reacted with 3-bromo-1-propylene and aminotri(methylene)phosphonic acid in sequence to graft phosphorus onto polyethylene and make it rich in quaternary ammonium salts. Organic phosphorus can be heated to carbonize the polymer into a dense and flame-retardant carbonized layer. The carbonized layer has excellent thermal insulation properties, can effectively reduce the speed of heat transfer to the interior of the material, and delay the development of the fire. In addition, the carbonized layer can prevent oxygen from contacting the internal material. , thereby inhibiting the combustion reaction, preventing the material from further pyrolysis and then terminating the combustion of the material, thereby improving the flame retardant ability of the material; quaternary ammonium salts can attract the negatively charged components on the cell membrane, destroy the integrity of the cell membrane, and cause the overflow of intracellular substances, and can also combine with enzymes to interfere with biochemical reactions and cause cell death. They can also combine with DNA or RNA to destroy its structure, causing cell death or functional damage, thereby achieving an antibacterial effect; functionalized halloysite nanotubes and modified polyethylene are mixed so that the functionalized halloysite nanotubes and modified polyethylene are combined in the form of ions, making the material easier to degrade. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0025] (1) Take 40 parts of polyethylene, 90 parts of xylene, 3 parts of diisopropylbenzene peroxide, and 8 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 70°C and 200 r / min for 10 minutes, heat to 120°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 30 minutes, stir at 250 r / min for 3 hours, cool to room temperature, filter, wash with acetone 3 times, vacuum dry at -10°C for 22 hours, and crush to 30 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 4:1:10, stir at 200 r / min and 70°C for 10 hours, filter, wash with methanol 3 times, and vacuum dry at -10°C for 22 hours to obtain modified polyethylene;

[0026] (2) The halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:15, stirred at 70°C and 200 r / min for 7 h, filtered, washed with deionized water for 3 times, vacuum dried at -10°C for 22 h, and ground to 80 mesh to obtain halloysite nanotube powder; the halloysite nanotube powder, deionized water and tea polyphenols were mixed in a mass ratio of 1:8:2, ultrasonicated at 0°C for 25 min, allowed to stand under vacuum for 25 min, returned to normal pressure, repeated the operation twice, centrifuged at 5000 r / min for 4 min, washed with ethanol for 3 times, vacuum dried at -10°C for 11 h, and ground to 30 mesh to obtain pre-modified halloysite nanotubes; pyrrole and propionic acid were mixed evenly in a volume ratio of 6:9 to obtain a pyrrole mixture; the pre-modified halloysite nanotubes, 4-(3 -thienyl)benzaldehyde and propionic acid were mixed in a mass ratio of 30:16:200, stirred at 138°C and 200r / min for 3min, a pyrrole mixture of 0.11 times the volume of propionic acid was added at a uniform rate within 25min, stirring was continued for 100min, cooled to room temperature, ethanol of 1.13 times the volume of propionic acid was added, allowed to stand at 0°C for 22h, filtered, washed with ethanol 3 times, and vacuum dried at -10°C for 22h to obtain modified halloysite nanotubes; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 1:3:2:1:9, stirred at 30°C, 200r / min, under nitrogen protection for 8min, filtered, allowed to stand at 60°C for 10h, and washed with deionized water 3 times to obtain functionalized halloysite nanotubes;

[0027] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:5:60:2.5, stirred at 200 r / min and 85°C for 3.5 h, filtered, washed with ethanol three times, dried at 85°C for 22 h, heated to 120°C, ultrasonicated for 8 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.03 mm. The mixture was allowed to stand for 22 h and scraped off to obtain an antibacterial packaging material.

[0028] Embodiment 2:

[0029] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0030] (1) Take 50 parts of polyethylene, 100 parts of xylene, 3.5 parts of diisopropylbenzene peroxide, and 9 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 75°C and 250 r / min for 15 minutes, heat to 130°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 20 minutes, stir at 300 r / min for 3.5 hours, cool to room temperature, filter, wash with acetone 4 times, vacuum dry at -5°C for 24 hours, and crush to 40 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 5:1:15, stir at 250 r / min and 80°C for 12 hours, filter, wash with methanol 4 times, and vacuum dry at -5°C for 23 hours to obtain modified polyethylene;

[0031] (2) The halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:16, stirred at 80°C and 250 r / min for 8 h, filtered, washed with deionized water for 4 times, vacuum dried at -5°C for 24 h, and ground to 100 mesh to obtain halloysite nanotube powder; the halloysite nanotube powder, deionized water and tea polyphenols were mixed in a mass ratio of 1:10:2.5, ultrasonicated at 2°C for 30 min, allowed to stand under vacuum for 27.5 min, returned to normal pressure, repeated the operation 3 times, centrifuged at 5000 r / min for 5 min, washed with ethanol for 4 times, vacuum dried at -5°C for 12 h, and ground to 40 mesh to obtain pre-modified halloysite nanotubes; pyrrole and propionic acid were mixed evenly in a volume ratio of 7:10 to obtain a pyrrole mixture; the pre-modified halloysite nanotubes, 4-( 3-thienyl)benzaldehyde and propionic acid are mixed in a mass ratio of 35:18:205, stirred at 140°C, 250r / min for 4min, 0.115 times the volume of propionic acid in pyrrole mixed solution is uniformly added within 30min, stirring is continued for 120min, cooled to room temperature, 1.14 times the volume of propionic acid in ethanol is added, standing at 2°C for 24h, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 23h to obtain modified halloysite nanotubes; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform are mixed in a mass ratio of 1:4:2.5:1:10, stirred at 35°C, 250r / min, under nitrogen protection for 9min, filtered, standing at 55°C for 12h, and washed with deionized water 4 times to obtain functionalized halloysite nanotubes;

[0032] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:6:62.5:3, stirred at 250 r / min and 90°C for 4 h, filtered, washed with ethanol 4 times, dried at 90°C for 24 h, heated to 130°C, ultrasonicated for 9 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.04 mm. The mixture was allowed to stand for 24 h and scraped off to obtain an antibacterial packaging material.

[0033] Embodiment 3:

[0034] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0035] (1) Take 60 parts of polyethylene, 110 parts of xylene, 4 parts of diisopropylbenzene peroxide, and 10 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 80°C and 300 r / min for 20 minutes, heat to 140°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 30 minutes, stir at 350 r / min for 4 hours, cool to room temperature, filter, wash with acetone 5 times, vacuum dry at 0°C for 26 hours, and crush to 50 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 6:1:20, stir at 300 r / min and 90°C for 14 hours, filter, wash with methanol 5 times, and vacuum dry at 0°C for 24 hours to obtain modified polyethylene;

[0036] (2) The halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:17, stirred at 90°C and 300 r / min for 9 h, filtered, washed with deionized water for 5 times, vacuum dried at 0°C for 26 h, and ground to 120 mesh to obtain halloysite nanotube powder; the halloysite nanotube powder, deionized water and tea polyphenols were mixed in a mass ratio of 1:12:3, ultrasonicated at 4°C for 35 min, allowed to stand under vacuum for 30 min, returned to normal pressure, repeated the operation 4 times, centrifuged at 5000 r / min for 6 min, washed with ethanol for 5 times, vacuum dried at 0°C for 13 h, and ground to 50 mesh to obtain pre-modified halloysite nanotubes; pyrrole and propionic acid were mixed in a volume ratio of 8:11 to obtain a pyrrole mixture; the pre-modified halloysite nanotubes, 4-(3 -thienyl)benzaldehyde and propionic acid were mixed in a mass ratio of 40:20:210, stirred at 142°C, 300r / min for 5min, a pyrrole mixture of 0.12 times the volume of propionic acid was uniformly added within 35min, stirring was continued for 140min, cooled to room temperature, ethanol of 1.15 times the volume of propionic acid was added, allowed to stand at 4°C for 26h, filtered, washed with ethanol 5 times, and vacuum dried at 0°C for 24h to obtain modified halloysite nanotubes; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 1:5:3:1:11, stirred at 40°C, 300r / min, under nitrogen protection for 10min, filtered, allowed to stand at 60°C for 14h, and washed with deionized water 5 times to obtain functionalized halloysite nanotubes;

[0037] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:7:65:3.5, stirred at 300 r / min and 95°C for 4.5 h, filtered, washed with ethanol 5 times, dried at 95°C for 26 h, heated to 140°C, ultrasonicated for 10 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.05 mm. The mixture was allowed to stand for 26 h and scraped off to obtain an antibacterial packaging material.

[0038] Comparative Example 1:

[0039] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0040] (1) Washing shiitake mushrooms with deionized water for 6 times, drying them by infrared at 55°C for 24 hours, grinding them into 80 meshes to obtain shiitake mushroom powder, mixing the shiitake mushroom powder with a 70% ethanol aqueous solution at a mass ratio of 1:16, stirring them at 50°C and 75 r / min for 1.5 hours, filtering the filtrate, centrifuging them at 4000 r / min for 20 minutes, and taking the supernatant to obtain tea polyphenols;

[0041] (2) The halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:16, stirred at 80°C and 250 r / min for 8 h, filtered, washed with deionized water for 4 times, vacuum dried at -5°C for 24 h, and ground to 100 mesh to obtain halloysite nanotube powder; the halloysite nanotube powder, deionized water and tea polyphenols were mixed in a mass ratio of 1:10:2.5, ultrasonicated at 2°C for 30 min, allowed to stand under vacuum for 27.5 min, returned to normal pressure, repeated the operation 3 times, centrifuged at 5000 r / min for 5 min, washed with ethanol for 4 times, vacuum dried at -5°C for 12 h, and ground to 40 mesh to obtain pre-modified halloysite nanotubes; pyrrole and propionic acid were mixed evenly in a volume ratio of 7:10 to obtain a pyrrole mixture; the pre-modified halloysite nanotubes, 4-( 3-thienyl)benzaldehyde and propionic acid are mixed in a mass ratio of 35:18:205, stirred at 140°C, 250r / min for 4min, 0.115 times the volume of propionic acid in pyrrole mixed solution is uniformly added within 30min, stirring is continued for 120min, cooled to room temperature, 1.14 times the volume of propionic acid in ethanol is added, standing at 2°C for 24h, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 23h to obtain modified halloysite nanotubes; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform are mixed in a mass ratio of 1:4:2.5:1:10, stirred at 35°C, 250r / min, under nitrogen protection for 9min, filtered, standing at 55°C for 12h, and washed with deionized water 4 times to obtain functionalized halloysite nanotubes;

[0042] (3) Functionalized halloysite nanotubes, polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:6:62.5:3, stirred at 250 r / min and 90°C for 4 h, filtered, washed with ethanol 4 times, dried at 90°C for 24 h, heated to 130°C, ultrasonicated for 9 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.04 mm. The mixture was allowed to stand for 24 h and scraped off to obtain an antibacterial packaging material.

[0043] Comparative Example 2:

[0044] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0045] (1) Take 50 parts of polyethylene, 100 parts of xylene, 3.5 parts of diisopropylbenzene peroxide, and 9 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 75°C and 250 r / min for 15 minutes, heat to 130°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 20 minutes, stir at 300 r / min for 3.5 hours, cool to room temperature, filter, wash with acetone 4 times, vacuum dry at -5°C for 24 hours, and crush to 40 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 5:1:15, stir at 250 r / min and 80°C for 12 hours, filter, wash with methanol 4 times, and vacuum dry at -5°C for 23 hours to obtain modified polyethylene;

[0046] (2) Halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:16, stirred at 80°C and 250 r / min for 8 h, filtered, washed with deionized water 4 times, vacuum dried at -5°C for 24 h, and ground into 100 mesh to obtain halloysite nanotube powder; pyrrole and propionic acid were mixed in a volume ratio of 7:10 to obtain a pyrrole mixed solution; halloysite nanotube powder, 4-(3-thienyl)benzaldehyde and propionic acid were mixed in a mass ratio of 35:18:205, stirred at 140°C and 250 r / min for 4 min, and propionic acid was added at a constant rate of 0.01% by volume over 30 min. .115 times the volume of pyrrole mixture, continue stirring for 120 minutes, cool to room temperature, add ethanol with a volume of 1.14 times that of propionic acid, stand at 2°C for 24 hours, filter, wash with ethanol 4 times, and vacuum dry at -5°C for 23 hours to obtain modified halloysite nanotubes; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform are mixed in a mass ratio of 1:4:2.5:1:10, stirred at 35°C, 250r / min, under nitrogen protection, for 9 minutes, filtered, stood at 55°C for 12 hours, and washed with deionized water 4 times to obtain functionalized halloysite nanotubes;

[0047] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:6:62.5:3, stirred at 250 r / min and 90°C for 4 h, filtered, washed with ethanol 4 times, dried at 90°C for 24 h, heated to 130°C, ultrasonicated for 9 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.04 mm. The mixture was allowed to stand for 24 h and scraped off to obtain an antibacterial packaging material.

[0048] Comparative Example 3:

[0049] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0050] (1) Take 50 parts of polyethylene, 100 parts of xylene, 3.5 parts of diisopropylbenzene peroxide, and 9 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 75°C and 250 r / min for 15 minutes, heat to 130°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 20 minutes, stir at 300 r / min for 3.5 hours, cool to room temperature, filter, wash with acetone 4 times, vacuum dry at -5°C for 24 hours, and crush to 40 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 5:1:15, stir at 250 r / min and 80°C for 12 hours, filter, wash with methanol 4 times, and vacuum dry at -5°C for 23 hours to obtain modified polyethylene;

[0051] (2) The halloysite nanotubes were mixed with 4M hydrochloric acid solution in a mass ratio of 1:16, stirred at 80°C and 250 r / min for 8 h, filtered, washed with deionized water for 4 times, vacuum dried at -5°C for 24 h, and ground to 100 mesh to obtain halloysite nanotube powder; the halloysite nanotube powder, deionized water and tea polyphenols were mixed in a mass ratio of 1:10:2.5, ultrasonicated at 2°C for 30 min, allowed to stand under vacuum for 27.5 min, returned to normal pressure, repeated the operation 3 times, centrifuged at 5000 r / min for 5 min, washed with ethanol for 4 times, vacuum dried at -5°C for 12 h, and ground to 40 mesh to obtain pre-modified halloysite nanotubes; pyrrole and propionic acid were mixed evenly in a volume ratio of 7:10 to obtain a pyrrole mixture; the pre-modified halloysite Nanotubes, 4-(3-thienyl)benzaldehyde and propionic acid were mixed in a mass ratio of 35:18:205, stirred at 140°C and 250r / min for 4min, a pyrrole mixture with a volume of 0.115 times that of propionic acid was added at a uniform rate within 30min, and stirring was continued for 120min, cooled to room temperature, ethanol with a volume of 1.14 times that of propionic acid was added, and the mixture was allowed to stand at 2°C for 24h, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 23h to obtain modified halloysite nanotubes; modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 2.5:1:10, stirred at 35°C, 250r / min, under nitrogen protection for 9min, filtered, allowed to stand at 55°C for 12h, and washed with deionized water 4 times to obtain functionalized halloysite nanotubes;

[0052] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:6:62.5:3, stirred at 250 r / min and 90°C for 4 h, filtered, washed with ethanol 4 times, dried at 90°C for 24 h, heated to 130°C, ultrasonicated for 9 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.04 mm. The mixture was allowed to stand for 24 h and scraped off to obtain an antibacterial packaging material.

[0053] Comparative Example 4:

[0054] A method for preparing an antibacterial packaging material mainly comprises the following preparation steps:

[0055] (1) Take 50 parts of polyethylene, 100 parts of xylene, 3.5 parts of diisopropylbenzene peroxide, and 9 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 75°C and 250 r / min for 15 minutes, heat to 130°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 20 minutes, stir at 300 r / min for 3.5 hours, cool to room temperature, filter, wash with acetone 4 times, vacuum dry at -5°C for 24 hours, and crush to 40 mesh to obtain pre-modified polyethylene; mix the pre-modified polyethylene, aminotrimethylenephosphonic acid and N-methylpyrrolidone in a mass ratio of 5:1:15, stir at 250 r / min and 80°C for 12 hours, filter, wash with methanol 4 times, and vacuum dry at -5°C for 23 hours to obtain modified polyethylene;

[0056] (2) Mixing halloysite nanotubes with 4M hydrochloric acid solution in a mass ratio of 1:16, stirring at 80°C and 250 r / min for 8 h, filtering, washing with deionized water 4 times, vacuum drying at -5°C for 24 h, grinding to 100 mesh, and obtaining halloysite nanotube powder; mixing halloysite nanotube powder, deionized water and tea polyphenols in a mass ratio of 1:10:2.5, ultrasonicating at 2°C for 30 min, standing under vacuum conditions for 27.5 min, returning to normal pressure, and repeating the operation 3 times. The mixture was centrifuged at 5000 r / min for 5 min, washed with ethanol for 4 times, vacuum dried at -5°C for 12 h, and ground to 40 mesh to obtain pre-modified halloysite nanotubes; 3-aminothiophene, thiophene, pre-modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 1:4:2.5:1:10, stirred at 35°C, 250 r / min, under nitrogen protection for 9 min, filtered, allowed to stand at 55°C for 12 h, and washed with deionized water for 4 times to obtain functionalized halloysite nanotubes;

[0057] (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water were mixed in a mass ratio of 1:6:62.5:3, stirred at 250 r / min and 90°C for 4 h, filtered, washed with ethanol 4 times, dried at 90°C for 24 h, heated to 130°C, ultrasonicated for 9 min, and evenly coated on the surface of a clean glass sheet with a thickness of 0.04 mm. The mixture was allowed to stand for 24 h and scraped off to obtain an antibacterial packaging material.

[0058] Test Example 1:

[0059] Flame retardancy test

[0060] The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.

[0061] Table 1

[0062] Limiting oxygen index Example 1 28.5% Example 2 28.8% Example 3 28.9% Comparative Example 1 21.8% Comparative Example 2 28.7% Comparative Example 3 28.4% Comparative Example 4 28.6%

[0063] From the comparison of the experimental data in Table 1, it can be found that the antibacterial packaging material prepared by the present invention has good flame retardancy.

[0064] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 1, which shows that the organic phosphorus can be heated to promote the carbonization of the polymer into a dense and flame-retardant carbonized layer. The carbonized layer has excellent thermal insulation properties and can effectively reduce the speed of heat transfer to the interior of the material and delay the development of the fire. In addition, the carbonized layer can also prevent oxygen from contacting the internal material, thereby inhibiting the combustion reaction, preventing the material from further pyrolysis and then terminating the combustion of the material, thereby improving the flame retardant ability of the material.

[0065] Test Example 2:

[0066] Antimicrobial testing

[0067] The test was conducted according to GB / T31402-2015 standard, where the selected bacteria were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.

[0068] Table 2

[0069]

[0070] From the comparison of the experimental data in Table 2, it can be found that the antibacterial packaging material prepared by the present invention has good antibacterial ability.

[0071] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 1, which shows that quaternary ammonium salts can attract the negatively charged components on the cell membrane, destroy the integrity of the cell membrane, and cause the intracellular substances to overflow, and can also bind to enzymes to interfere with biochemical reactions and cause cell death. It can also bind to DNA or RNA to destroy its structure, causing cell death or functional impairment, thereby achieving an antibacterial effect.

[0072] Test Example 3:

[0073] Antistatic test

[0074] The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 3.

[0075] Table 3

[0076] Surface resistivity Example 1 <![CDATA[1.593*10 9 Oh]]> Example 2 <![CDATA[1.533*10 9 Oh]]> Example 3 <![CDATA[1.556*10 9 Oh]]> Comparative Example 1 <![CDATA[1.667*10 9 Oh]]> Comparative Example 2 <![CDATA[1.512*10 9 Oh]]> Comparative Example 3 <![CDATA[2.566*10 12 Oh]]> Comparative Example 4 <![CDATA[1.583*10 9 Oh]]>

[0077] From the comparison of the experimental data in Table 3, it can be found that the antibacterial packaging material prepared by the present invention has good antistatic ability.

[0078] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 3, it can be found that the surface resistivity of Examples 1, 2, 3 is smaller than that of Comparative Example 3, which shows that polythiophene, as a conductive polymer, can absorb and transfer charges through its conductivity and high conductivity, reduce the cumulative effect of static electricity, and thus achieve an antistatic effect.

[0079] Test Example 4

[0080] Degradation test

[0081] An artificial accelerated ultraviolet degradation test was carried out using a LUV-1 ultraviolet aging test box. The films prepared in the embodiments and comparative examples were cut into samples with a length of 50 cm and a width of 8 cm, and placed under a lamp for irradiation. The films were distributed in the effective light area of ​​the film frame, and the distance from the lamp tube was 14.5 cm. The ambient temperature was 25°C. After the samples were irradiated for 144 hours, the infrared spectrum of the films was measured using a Fourier transform infrared spectrometer FTIR. The infrared spectrum of the samples at 1715 cm -1 The infrared characteristic absorption peak of the sample is used to calculate the carbonyl index, where the carbonyl index is

[0082] =A1715 / A2020. The results are shown in Table 4.

[0083] Table 4

[0084] Carbonyl Index Example 1 33.6 Example 2 34.1 Example 3 33.8 Comparative Example 1 33.4 Comparative Example 2 33.7 Comparative Example 3 33.3 Comparative Example 4 12.3

[0085] From the comparison of the experimental data in Table 4, it can be found that the antibacterial packaging material prepared by the present invention has good degradability.

[0086] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 4, it can be found that the carbonyl index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which indicates that the iron ions in the ferric chloride catalyst used for polythiophene polymerization can combine with the MOF structure and degrade the polymer under photocatalysis.

[0087] Test Example 5

[0088] Long-term antioxidant test

[0089] Weigh 0.5g of the film, cut it into pieces and soak it in 10mL of ethanol, place it in a 37°C shaking incubator and seal it for storage. After 24h and 144h, take 1mL of the supernatant and add it to the prepared 1mL of 0.1mmol / L DPPH ethanol solution, mix it thoroughly, and let it stand in the dark at room temperature for 60 minutes. Use an ultraviolet spectrophotometer to test it. The free radical scavenging ability of the active film is characterized by the change in absorbance at a wavelength of 517nm. DPPH free radical scavenging rate = (absorbance of blank DPPH ethanol solution - absorbance of DPPH ethanol solution after adding supernatant) / absorbance of blank DPPH ethanol solution * 100%. The results are shown in Table 5.

[0090] Table 5

[0091] DPPH free radical scavenging rate (24h) DPPH free radical scavenging rate (144h) Example 1 58.9% 60.3% Example 2 59.3% 60.5% Example 3 59.0% 60.4% Comparative Example 1 58.8% 60.6% Comparative Example 2 0.8% 0.7% Comparative Example 3 59.2% 60.1% Comparative Example 4 59.0% 60.2%

[0092] From the comparison of the experimental data in Table 5, it can be found that the antibacterial packaging material prepared by the present invention has good long-term antioxidant ability.

[0093] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 5, it can be found that the DPPH radical scavenging rates of Examples 1, 2, 3 are greater than that of Comparative Example 2, which shows that tea polyphenols have a good antioxidant effect. The specific surface area of ​​the halloysite nanotubes after acid etching is increased, and more phenolic substances in tea polyphenols can be loaded inside them, achieving the effect of long-acting sustained-release antioxidants.

[0094] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An antibacterial packaging material, characterized in that: The antibacterial packaging material is prepared by mixing functionalized halloysite nanotubes and modified polyethylene, heating, and forming a film; The modified polyethylene is prepared by reacting polyethylene with 3-bromo-1-propylene and aminotri(methylenephosphonic acid) in sequence; The functionalized halloysite nanotubes are prepared by etching the halloysite nanotubes with hydrochloric acid solution, loading tea polyphenols inside the halloysite nanotubes, reacting 4-(3-thienyl)benzaldehyde and pyrrole on the surface of the nanotubes, and finally polymerizing with 3-aminothiophene and thiophene.

2. A method for preparing an antibacterial packaging material, characterized in that: The preparation method of the antibacterial packaging material mainly includes the following preparation steps: (1) Take 40-60 parts of polyethylene, 90-110 parts of xylene, 3-4 parts of diisopropylbenzene peroxide, and 8-10 parts of 3-bromo-1-propylene by weight, mix the polyethylene and xylene, stir at 70-80°C and 200-300 r / min for 10-20 min, raise the temperature to 120-140°C under nitrogen protection, add 3-bromo-1-propylene, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 10-30 min, stir at 250-350 r / min for 30 min. ~4h, cooled to room temperature, filtered, washed with acetone 3~5 times, vacuum dried at -10~0℃ for 22~26h, crushed to 30~50 mesh, and obtained pre-modified polyethylene; pre-modified polyethylene, aminotri(methylenephosphonic acid) and N-methylpyrrolidone were mixed in a mass ratio of 4~6:1:10~20, stirred at 200~300r / min, 70~90℃ for 10~14h, filtered, washed with methanol 3~5 times, vacuum dried at -10~0℃ for 22~24h, and obtained modified polyethylene; (2) mixing halloysite nanotubes with hydrochloric acid solution in a mass ratio of 1:15-17, stirring at 70-90°C and 200-300 r / min for 7-9 hours, filtering, washing with deionized water for 3-5 times, vacuum drying at -10-0°C for 22-26 hours, grinding to 80-120 meshes, and obtaining halloysite nanotube powder; mixing halloysite nanotube powder, deionized water and tea polyphenols in a mass ratio of 1:8-12:2-3, and evaporating at 0-4°C. The method comprises the following steps: ultrasonicating for 25 to 35 minutes, standing under vacuum for 25 to 30 minutes, returning to normal pressure, repeating the operation 2 to 4 times, centrifuging at 5000 r / min for 4 to 6 minutes, washing with ethanol for 3 to 5 times, vacuum drying at -10 to 0°C for 11 to 13 hours, grinding to 30 to 50 meshes, and preparing pre-modified halloysite nanotubes; mixing the pre-modified halloysite nanotubes, 4-(3-thienyl)benzaldehyde and propionic acid in a mass ratio of 30 to 40:16 to 20 : 200-210, stir at 138-142°C, 200-300r / min for 3-5min, add 0.11-0.12 times the volume of propionic acid in pyrrole mixture at a uniform rate within 25-35min, continue stirring for 100-140min, cool to room temperature, add 1.13-1.15 times the volume of propionic acid in ethanol, let stand at 0-4°C for 22-26h, filter, wash with ethanol 3-5 times, and freeze at -10-0°C The modified halloysite nanotubes were prepared by vacuum drying for 22 to 24 hours; 3-aminothiophene, thiophene, modified halloysite nanotubes, ferric chloride and chloroform were mixed in a mass ratio of 1:3 to 5:2 to 3:1 to 9 to 11, stirred for 8 to 10 minutes at 30 to 40°C, 200 to 300 r / min, and nitrogen protection, filtered, allowed to stand at 50 to 60°C for 10 to 14 hours, and washed with deionized water for 3 to 5 times to obtain functionalized halloysite nanotubes; (3) Functionalized halloysite nanotubes, modified polyethylene, ethanol and deionized water are mixed in a mass ratio of 1:5-7:60-65:2.5-3.5, stirred at 200-300 r / min and 85-95° C. for 3.5-4.5 h, filtered, washed with ethanol 3-5 times, dried, heated to 120-140° C., ultrasonicated for 8-10 min, and film-formed to obtain an antibacterial packaging material.

3. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The concentration of the hydrochloric acid solution in step (2) is 4M.

4. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The tea polyphenols in step (2) are 98% water-soluble tea polyphenols.

5. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The pyrrole mixed solution in step (2) is prepared by uniformly mixing pyrrole and propionic acid in a volume ratio of 6-8:9-11.

6. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The repeated operation in step (2) refers to repeatedly standing under vacuum conditions for 25 to 30 minutes and returning to normal pressure.

7. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The specific operation of the film-making in step (3) is to evenly coat the film on the surface of a clean glass sheet with a thickness of 0.03 to 0.05 mm, let it stand for 22 to 26 hours, and then scrape it off.

8. The method for preparing an antibacterial packaging material according to claim 2, characterized in that: The specific operation of the drying in step (3) is drying at 85-95° C. for 22-26 hours.

Citation Information

Patent Citations

  • Process for grafting solution after polymerization

    CN109593162A

  • Lignin-based flame retardant containing nitrogen and phosphorus elements as well as preparation method and application of lignin-based flame retardant

    CN112961372A

  • Bio-based antibacterial fiber and preparation method thereof

    CN118531521A

  • Bio-based modified regenerated plastic and preparation method thereof

    CN118599251A

  • Anti-static plastic packaging film and preparation method thereof

    CN119019718A

Cited By

  • High-heat-resistance PLA / PBS biodegradable composite material and preparation method thereof

    CN120574471A

  • Permeable asphalt composition and preparation method thereof

    CN120622846A

  • A permeable asphalt composition and a method for preparing the same

    CN120622846B

  • Flame-retardant environment-friendly high-flexibility drag chain cable and preparation process thereof

    CN120895303A